Tin (IV) alkoxide initiator design for poly (d-lactide) synthesis using DFT calculations - Narin Lawan (2018)
The ring-opening polymerization (ROP) mechanism of d-lactide using tin (IV) alkoxides, (CH 3 (CH 2 ) 3 ) 3 SnOR, as initiators was theoretically studied. The high level adiabatic mapping B3LYP/LANL2DZ calculations were performed. This work evaluates role of the tin (IV) alkoxide initiators and gives molecular detail of the polymerization mechanism. In order to investigate the effects of the substituent (R) group of initiator on the ROP reaction rate, the R group was modeled to be linear R groups; -CH 2 CH 3 , -(CH 2 ) 3 CH 3 , -(CH 2 ) 5 CH 3 , -(CH 2 ) 7 CH 3 , -(CH 2 ) 9 CH 3 and branch R groups; -CH 2 CH 3 , -CH 2 CH(CH 3 ) 2 , -C(CH 3 ) 3 . The calculations show that the rate limiting step of the ROP reaction mechanism is the first transition state (TS1) of the reaction which corresponds to the steric effect of the initiators. For the initiators with a linear R group, the steric effect on the potential energy barrier of the TS1 is not significant whereas the initiators with branch R groups relatively increase the potential energy barrier. However, the determined potential energies of the TS1 for most initiators studied in the work are in the same range (16.0-20.2kcal/mol). Therefore, all the initiators except (CH 3 (CH 2 ) 3 ) 3 SnOC(CH 3 ) 3 are suitable for the ROP of the d-lactide. © 2013 Elsevier B.V.